Sistem Pendukung Keputusan Penilaian Kinerja Dosen Menggunakan Metode AHP di STIMIK Sepuluh Nopember Jayapura - Patmawati Hasan; Ema Utami; Asro Nasiri (Maranatha University Press, 2018)
Lecturers are an important component in the education system in higher education. As mandated in Law No. 14 of 2005 concerning Teachers and Lecturers, lecturers were declared as professional educators and scientists with the main task of transforming, developing, and disseminating knowledge, information, technology and art through education, research, and community service (Chapter 1 Article 1 paragraph 2). To measure lecturer performance, it is necessary to assess the performance of the lecturer. In assessing the performance of lecturers in the Informatics Engineering Study Program there are several criteria assessed. This assessment is based on the criteria for teaching and learning, research, community service and attendance at STIMIK Ten November November using the AHP method. And with an alternative, the permanent lecturer is STIMIK Sepuluh Nopember Teknik Informatika Jayapura. In a study of Decision Support Systems Lecturer Performance Assessment Using AHP Method in STIMIK Ten November Jayapura by conducting observations and interviews and weighting criteria and alternative values based on observation and interviews. Decision Support System Assessment of Lecturer Performance Using AHP Method is designed using the PHP programming language and MySQL Database.